Both immediate and delayed intracavernous injections of autologous adipose-derived stromal vascular fraction enhance recovery of erectile function in a rat model of cavernous nerve injury - Qiu, Xuefeng (2012)
BACKGROUND: Intracavernous injection of cultured adipose tissue-derived stem cells (ADSCs) effectively restores erectile function in cavernous nerve (CN) injured rats when administered at the time of injury. However, culturing exposes ADSCs to risks of contamination and dedifferentiation. Furthermore, the acute treatment paradigm precludes selecting the patient subset benefitting from the treatment the most. OBJECTIVES: To explore the effect of uncultured autologous adipose-derived stromal vascular fraction (SVF) on improving erectile function in a rat model of CN injury when administered at the time of injury or four weeks post-injury. DESIGN, SETTING, AND INTERVENTIONS: Sixty-three male Sprague-Dawley rats were randomly divided into three groups: intracavernous injection of saline immediately after CN crush (vehicle), intracavernous injection of SVF immediately after CN crush (immediate-treatment), intracavernous injection of SVF four weeks post-CN crush (delayed-treatment). Twenty-six animals underwent sham surgery (sham). Functional testing and histological analysis were performed 12 weeks post-CN crush or sham surgery. MEASUREMENTS: Intracavernous pressure (ICP) response to CN electrostimulation, histological examination of midpenile cross-sections. RESULTS: Intracavernous injection of SVF, either immediately, or four weeks post-CN injury, resulted in significantly increased ICP/mean arterial pressure (MAP) ratios compared with the vehicle-treated group. Both immediate and delayed treatment with SVF significantly increased expression of neuronal nitric oxide synthase (nNOS) and neurofilament (NF) in dorsal penile nerves compared to the vehicle group. Furthermore, smooth muscle content and smooth muscle/collagen ratio within corpus cavernosum were significantly improved in both SVF treatment groups compared to vehicle-treated rats. CONCLUSIONS: Uncultured autologous SVF injected immediately or 4 weeks post-CN crush improved erectile function, promoted nerve regeneration and prevented fibrosis of the corpus cavernosum following CN injury. The clinical availability of routine SVF isolation devices merits testing autologous SVF therapy in penile rehabilitation studies following radical prostatectomy in the near future.